Levels of selected persistent organic pollutants in blood from delivering women in seven selected areas of São Paulo State, Brazil - Rudge, Cibele Vieira Cunha [UNESP]; Sandanger, Torkjel; Roellin, Halina B.; Calderon, Iracema de Mattos Paranhos [UNESP]; Volpato, Gustavo Tadeu [UNESP]; Silva, Joao L. P.; Duarte, Geraldo; Neto, Corintio M.; Sass, Nelson; Nakamura, Mary U.; Odland, Jon O.; Rudge, Marilza Vieira Cunha [UNESP] (Pergamon-Elsevier B.V. Ltd, 2012)
Persistent organic pollutants (POPS) present in the living environment are thought to have detrimental health effects on the population, with pregnant women and the developing foetus being at highest risk. We report on the levels of selected POPs in maternal blood of 155 delivering women residing in seven regions within the São Paulo State, Brazil.The following selected POPs were measured in the maternal whole blood: 12 polychlorinated biphenyls (PCBs) congeners (IUPAC Nos. 99, 101, 118, 138, 153, 156, 163, 170, 180, 183, 187, 194); dichlordiphenyltrichloroethane p,p'-DDT, diphenyldichloroethylene p,p'-DDE and other pesticides such as hexachlorocyclohexanes (alpha-HCH, beta-HCH, gamma-HCH), hexachlorobenzene (HCB), chlordane derivatives cis-chlordane, trans-chlordane. oxy-chlordane, cis-nonachlor and trans-nonachlor.Statistical comparisons between regions were performed only on compounds having concentrations above LOD in 70% of the samples. PCB118 congener was found to be highest in the industrial site (mean 4.97 ng/g lipids); PCB138 congener concentration was highest in the Urban 3 site (mean 4.27 ng/g lipids) and congener PCB153 was highest in the industrial and Urban 3 sites with mean concentration of 7.2 ng/g lipids and 5.89 ng/g lipids respectively. Large differences in levels of p,p'-DDE between regions were observed with the Urban 3 and industrial sites having the highest concentrations of 645 ng/g lipids and 417 ng/g lipids, respectively; beta-HCH was found to be highest in the Rural 1 site; the gamma-HCH in Rural 1 and industrial; the HCB in the Rural 1 and industrial sites and oxy-chlordane and t-NC in the Rural 2 sites. An association between levels of some contaminants and maternal age and parity was also found. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Pesticides exposure; Delivering women; Human blood; São Paulo State; Brazil